2017
DOI: 10.3415/vcot-17-01-0014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of T2 Relaxation Times for Normal Canine Knee Articular Cartilage by T2 Mapping Using 1.5-T Magnetic Resonance Imaging

Abstract: This study aims to assess and compare the T2 relaxation times for articular cartilage of normal canine stifle joints in four regions by T2 mapping using a 1.5-T magnetic resonance imaging (MRI). prospective study: 20 hindlimbs (left and right) from 10 normal healthy beagle dogs ( = 20). The region of interest (ROI) was subdivided into medial and lateral condyles of femoral cartilage (MF and LF, respectively) and medial and lateral condyles of tibial cartilage (MT and LT, respectively). The T2 relaxation times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Currently, apart from the manufacturer's instructions, there are no guidelines regarding the positioning of the dog for knee imaging. In other articles, dogs were placed in the dorsal (2,5,12,23,24,32,40,43,44) lateral (4,11,36,37) or bridge position (15).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, apart from the manufacturer's instructions, there are no guidelines regarding the positioning of the dog for knee imaging. In other articles, dogs were placed in the dorsal (2,5,12,23,24,32,40,43,44) lateral (4,11,36,37) or bridge position (15).…”
Section: Discussionmentioning
confidence: 99%
“…In total there have been four previous studies in which T2 relaxation times have been quantified in dogs. Two of these studies evaluated normal dog knees, one study used normal canine elbows, and there was the aforementioned study that evaluated both normal dog knees and knees in which a subchondral bone defect had been created . The mean T2 value for two of these studies were 52–70 ms while the mean T2 values for the other two studies were 28–48 ms .…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies evaluated normal dog knees, one study used normal canine elbows, and there was the aforementioned study that evaluated both normal dog knees and knees in which a subchondral bone defect had been created . The mean T2 value for two of these studies were 52–70 ms while the mean T2 values for the other two studies were 28–48 ms . The range in meant T2 relaxation times in the current study were 52–66 ms (Table ) and thus fall within the range of T2 values previously reported in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation